MODELS OF DEFINED CONTRIBUTION PENSION SYSTEMS IN FOREIGN COUNTRIES - Kazbekova L.,; Kurmangali A.,; Yerniyazova Zh.,; Akhmetova A.,; Utegenova K., (Academic Journal of Physical and Chemical Sciences, 2020)
The paper is focused on the analysis of the foreign experience in the field of creation and reforming of the pension systems. The paper is aimed at studying the economic bases of the forming of defined contribution pension systems in foreign countries and revealing of the main tendencies in pension reforms in foreign countries to define the possibilities of the pension reform for Kazakhstan. To achieve the set goal the paper investigates the main types of the pension system and its existing levels. The analysis of the stated elements of the pension system was based on the example of the countries of the Organization of Economic Cooperation and Development. The conducted investigation allowed revealing the advantages and disadvantages of the pay-as-you-go, defined contribution, and mixed pension schemes. Basing on the conclusion on the necessity to use the foreign experience in implementing the Kazakhstan pension reform, the concrete trends of its further reforming aimed at improving the effectiveness of the Kazakhstan pension system and its approach to the worldwide standards were proposed. The investigation results can be used for developing the program documents defining the strategy of the pension schemes development under the contemporary economic and demographic conditions. The conclusions and recommendations on the pension scheme improving proposed in the work can be used for the pension reform in Kazakhstan.